Optimized depletion of chimeric antigen receptor T cells in murine xenograft models of human acute myeloid leukemia - Tasian, Sarah K. (Blood, 2017)
We and others previously reported potent antileukemia efficacy of CD123-redirected chimeric antigen receptor (CAR) T cells in preclinical human acute myeloid leukemia (AML) models at the cost of severe hematologic toxicity. This observation raises concern for potential myeloablation in patients with AML treated with CD123-redirected CAR T cells and mandates novel approaches for toxicity mitigation. We hypothesized that CAR T-cell depletion with optimal timing after AML eradication would preserve leukemia remission and allow subsequent hematopoietic stem cell transplantation. To test this hypothesis, we compared 3 CAR T-cell termination strategies: (1) transiently active anti-CD123 messenger RNA–electroporated CART (RNA-CART123); (2) T-cell ablation with alemtuzumab after treatment with lentivirally transduced anti–CD123-4-1BB-CD3ζ T cells (CART123); and (3) T-cell ablation with rituximab after treatment with CD20-coexpressing CART123 (CART123-CD20). All approaches led to rapid leukemia elimination in murine xenograft models of human AML. Subsequent antibody-mediated depletion of CART123 or CART123-CD20 did not impair leukemia remission. Time-course studies demonstrated that durable leukemia remission required CAR T-cell persistence for 4 weeks prior to ablation. Upon CAR T-cell termination, we further demonstrated successful hematopoietic engraftment with a normal human donor to model allogeneic stem cell rescue. Results from these studies will facilitate development of T-cell depletion strategies to augment the feasibility of CAR T-cell therapy for patients with AML.